The Role of Corporate Governance on Stock Prices: Evidence from IPOs in Malaysia - Shaukenov, Arman (2009)
There is an assumption that corporate governance mechanisms can be used strategically to influence stock price performance and therefore shareholder value. This makes one to believe that publicly listed companies may employ sufficient level of corporate governance signals in order to communicate investors about their potential expertise and independence. Since, not much empirical literature exists after implementation of corporate governance reforms in Malaysia, the research paper attempts to fill this gap. Hence, the study investigates the relationship between the corporate governance structure and market value of 166 initial public offerings issued on Bursa Malaysia between 2001 and 2006. The empirical study reports that undertaken changes in regulatory and legal system are somewhat successful where most of the Malaysian listed companies increasingly adhere to principles and best practices set by regulators. However, the ownership concentration is found to be consistently high which is likely to repel smaller investors away from an emerging economy because this might create asymmetry information for them. Following investigation reveals that on average Malaysian IPOs tend to be highly under-priced. Meanwhile, the result on aftermarket performance in three-year time indicates steadily increasing cumulative mean abnormal return. These financial figures suggest that IPOs in Malaysia are profitable short and long-term investments where companies are exposed to lesser degree of under-pricing post issue. However, the regression analysis fails to demonstrate strong relationship between corporate governance mechanisms and initial return at the first trading day. This finding implies that the corporate governance structure is not critical factor for IPO investors. Moreover, the cumulative abnormal return does not show potential importance of corporate governance either, except for dual leadership structure though. The separation of roles of CEO and Chairman is robustly associated with the superior aftermarket stock performance.